Effects of Self-Concept and Emotional Intelligence Training on Occupational Stress of Public Secondary School Administrators in Southwestern, Nigeria (2015)
The duties and responsibilities as well as the work environment of contemporary public secondary school administrators in Southwestern Nigeria make them vulnerable to high level of occupational stress. This affects not only their mental and physical health but also the entire functioning of the secondary school system, raising concern among stakeholders. Previous studies have identified sources, dimensions and use of some psychological interventions in managing occupational stress with little or no consideration for the combined effects of self-concept and emotional intelligence trainings. This study, therefore, examined the effects of Self-concept Training (SCT) and Emotional Intelligence Training (EIT) on occupational stress of public secondary school administrators in Southwestern Nigeria. The moderating effects of self-efficacy and gender were also determined. The study adopted a pretest-posttest, control group, quasi experimental design using a 3x2x2 factorial matrix. Three non-randomised groups of All Nigerian Confederation of Principals of Secondary Schools (ANCOPSS) from Oyo (37), Osun (50) and Ogun (34) states were used. Participants were 47 males and 74 females with a mean age of 54 ± 2 years. The ANCOPSS groups were assigned to SCT (Oyo), EIT (Ogun) and control (Osun) groups and the treatment lasted eight weeks. Emotional Intelligence (r=0.97), Self-concept (r=0.88), Self-efficacy (r=0.79), School Administrator Occupational Stress Indicator (r=0.81) and School Administrator Stress Management (r=0.77) scales were used for data collection. Seven hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance, Multiple Classification Analysis and Scheffe post-hoc test. There was a significant main effect of treatment on occupational stress of participants (F(3; 117)=21.51, ŋ2=.27). The participants in EIT group (𝑥 =18.77) performed better than those in the SCT (𝑥 =17.37) and the control (𝑥 =13.23) groups. There was also a significant main effect of self-efficacy on occupational stress (F(2;118)=17.84, ŋ2=.13) but none for gender. Participants with medium self-efficacy (𝑥 =17.76) performed better than those with low self-efficacy (𝑥 =14.37). There was a significant two-way interaction effect of treatment and self-efficacy on occupational stress (F(2;114)=3.08, ŋ2=.05). However, there were no two-way interaction effects of treatment and gender, and gender and self-efficacy on occupational stress. The three-way interaction effect of treatment, gender and self-efficacy was also not significant. The self-concept training used in Oyo State and the emotional intelligence training employed in Ogun State were both effective in enhancing occupational stress management of public secondary school administrators. Therefore, the two strategies should be employed in assisting school administrators in coping with occupational stress.